The systematic investigations of high-pressure polymorphs in shocked ordinary chondrites - Miyahara, Masaaki; Yamaguchi, Akira; Saitoh, Masato; Fukimoto, Kanta; Sakai, Takeshi; Ohfuji, Hiroaki; Tomioka, Naotaka; Kodama, Yu; Ohtani, Eiji (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites / Hayabusa, Wed. 5 Dec. / Conference hall of the Research/Administration Building (2nd floor) at the JAXA Sagamihara Campus conference object